2017
DOI: 10.1111/age.12607
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and paternal origin of domestic donkeys

Abstract: Numerous studies have been conducted to investigate genetic diversity, origins and domestication of donkey using autosomal microsatellites and the mitochondrial genome, whereas the male-specific region of the Y chromosome of modern donkeys is largely uncharacterized. In the current study, 14 published equine Y chromosome-specific microsatellites (Y-STR) were investigated in 395 male donkey samples from China, Egypt, Spain and Peru using fluorescent labeled microsatellite markers. The results showed that seven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…3): cluster A included Kulun, Guanzhong, Liangzhou, and Xiji donkey breeds and cluster B gathered Dezhou, Gunsha, Biyang, and Taihang breeds, while other donkey breeds (Xinjiang, Qinghai, Qingyang, and Jiami) appeared to be the contact zone between both clusters, as individuals had mixed lineages. The results support the previous genetic research about the origin of the Chinese donkey, in which Chinese donkeys have two distinct mitochondrial maternal lineages, known as Nubian wild ass (Equus africanus africanus) and the Somali wild ass (Equus africanus somaliensis) (Lei et al, 2007;Han et al, 2014). When K = 3 ( Fig.…”
Section: Relationship Among 12 Chinese Native Donkey Breedssupporting
confidence: 90%
See 3 more Smart Citations
“…3): cluster A included Kulun, Guanzhong, Liangzhou, and Xiji donkey breeds and cluster B gathered Dezhou, Gunsha, Biyang, and Taihang breeds, while other donkey breeds (Xinjiang, Qinghai, Qingyang, and Jiami) appeared to be the contact zone between both clusters, as individuals had mixed lineages. The results support the previous genetic research about the origin of the Chinese donkey, in which Chinese donkeys have two distinct mitochondrial maternal lineages, known as Nubian wild ass (Equus africanus africanus) and the Somali wild ass (Equus africanus somaliensis) (Lei et al, 2007;Han et al, 2014). When K = 3 ( Fig.…”
Section: Relationship Among 12 Chinese Native Donkey Breedssupporting
confidence: 90%
“…Additionally, two main groups suggest that the colonization process and expansion of donkeys across China followed at least two main pathways. According to textual research and ancient DNA studies (Han et al, 2014), the earliest domestic Chinese donkeys were from the small donkeys of ancient Xinjiang and entered the mainland 2000 years ago (west Han Dynasty). They arrived in the Hexi Corridor of the northern Qilian Mountains along the Silk Road and then developed into Liangzhou donkeys.…”
Section: Relationship Among 12 Chinese Native Donkey Breedsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite this connection and the fact that chromosomal abnormalities in the horse are widely studied, donkey cytogenetics is still scarcely developed (Dorado et al, ). However, it was demonstrated that molecular analysis employed in horses could be successfully adapted to this species (Han et al, ).…”
Section: Introductionmentioning
confidence: 99%